2021
DOI: 10.3390/jcm10091911
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Human Papillomavirus Infection (HPV) and High Oncogenic Risk Genotypes among Women Living with HIV in Asia: A Meta-Analysis

Abstract: Women living with HIV (WLHIV) are prone to harbor several high-risk human papillomavirus (HR-HPV) genotypes and to develop cervical cancerous lesions. Data on HPV prevalence in these women are needed to inform immunization programs, especially in Asia where few data are available. We conducted a systematic review and meta-analysis to estimate the prevalence of HPV and HR-HPV cervical infection in WLHIV in Asia and identify possible sources of heterogeneity for HR-HPV carriage. Pooled prevalence and its 95% con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Approximately 70% of cervical cancer and pre-cancerous lesions are associated with HPV16 and HPV18 [ 14 ]. However, the predominant HPV genotypes may result in different outcomes at different stages of the disease [ 15 , 16 ]. HPV52 and HPV16 are dominant in CIN1, while HPV16 and HPV58 are found in CIN2/3 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 70% of cervical cancer and pre-cancerous lesions are associated with HPV16 and HPV18 [ 14 ]. However, the predominant HPV genotypes may result in different outcomes at different stages of the disease [ 15 , 16 ]. HPV52 and HPV16 are dominant in CIN1, while HPV16 and HPV58 are found in CIN2/3 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a homologous genus of HPV 18, HPV A7 is associated with cervical adenocarcinoma. As a homologous species of HPV16, HPV A9 is associated with cervical squamous cell carcinoma.At present, this HPV grouping method is rarely used in clinic, but some studies have found that HPV A7 has more integration sites than A9, and the prognosis of cervical cancer caused by A7 is worse[ 17 , 18 ].Although the integration rate of HPV A9 is lower than that of A7, the incidence of cervical cancer is higher [ 19 , 20 ], so we still need to pay attention to the infection of different HPV groups in the population.…”
Section: Discussionmentioning
confidence: 99%
“…In recognition of the differences in HPV prevalence, cervical cancer risk, and recommended screening intervals among WLWH, the CPPT disaggregates results in the screening approaches by HIV status. With high sensitivity but low specificity for CIN2 + , the implementation of HPV testing alone among WLWH, for whom HPV prevalence can be 50% or higher [28,29], can result in overtreatment due to the detection of otherwise transient HPV infections [30]. Countries with a high dual burden of HIV and cervical cancer will need different approaches for these women, such as a highly accurate triage test to further identify those needing treatment or more frequent screening among WLWH.…”
Section: Considerations For Selecting Cervical Cancer Screening and T...mentioning
confidence: 99%